Comparison of Rituximab originator (MabThera) to biosimilar (Truxima) in patients with immune‐mediated thrombotic thrombocytopenic purpura. (28th March 2019) - Stubbs, Matthew J.; Low, Ryan; McGuckin, Siobhan; Newton, Rosalind; Thomas, Mari; Westwood, John P.; Shah, Raakhee; Cheesman, Simon; Scully, Marie A.
Summary: Immune thrombotic thrombocytopenic purpura (iTTP) is an acute, multisystem thrombotic microangiopathy mediated by ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) autoantibodies. Immunosuppression with anti‐CD20 therapy is the mainstay of treatment. MabThera's patent has now expired and biosimilars have been approved. Eighty‐four consecutive patient episodes over 2 years, prior to and following our switch to Truxima are presented. Day 1 (D1), Day 28 (D28) and 3‐month platelet counts, ADAMTS13 activity, and CD19 levels, adverse reactions and infective complications were recorded. Platelet counts were not significantly different between acute MabThera and Truxima treatment (D1 P  = 0.085, D28 P  = 0.77, 3 months P  = 0.71) and electively (D1 P  = 0.79, D28 P  = 0.68, 3 months P  = 0.99). ADAMTS13 recovery also was not significantly different acutely (D1 P  = 0.99, D28 P  = 0.27, 3 months P  = 0.26) and electively (D1 P  = 0.59, D28 P  = 0.61, 3 months P  = 0.34). CD19% depletion at D1 and 3 months was not significantly different acutely (D1 P  = 0.52, 3 months P  = 0.56) and electively (D1 P  = 0.22, 3 months P  = 0.19). Infusion reactions and infective complications were comparable with both therapies. This is the first series of the Rituximab biosimilar Truxima to be reported in iTTP, demonstrating equivalence to MabThera in terms of ADAMTS13 recovery, CD19 depletion, and platelet count at D28 and 3 months post‐administration, with comparable infusion and infective complications. The financial benefit of the biosimilar anti‐CD20 is considerable.